Research on Composite Braking Mode Switching Strategy Based on Fuzzy Algorithm. Issue 2 (14th December 2022) - Zheng, Zhu'An; Liang, Cang; Lv, Hongming; Zhang, Kun; Zhang, Weiyang
Abstract: Aiming at the cruising range of electric vehicles, this paper proposes a control strategy for electric vehicle electromechanical composite braking mode switching based on motor braking force correction. The braking force of the motor is adjusted by factors such as braking intensity to improve the braking energy recovery, and the braking force distribution curve is designed considering the braking energy and braking safety and stability. The research results show the braking time, braking torque, and battery charge. The peak value of discharge current has been improved, and the braking energy recovery efficiency has increased by 9.17% and 3.32% respectively under different working conditions. Under different braking modes with an initial speed of 30 km h −1, the braking energy recovered by the battery has increased by 16.04 , 3.89, 9.63 kJ, the braking time and braking distance are also shorter, which highlights the superiority of this control strategy. Abstract : Amining at the problem of low energy recovery efficiency of electric vehicle, a composite braking control strategy based on braking mode switching is proposed to regulate the electric mechanism power by fuzzy algorithm. The results show that the optimized control strategy improves the braking energy recovery efficiency while ensuring safe and stable braking.